PEMBENTUKAN KARAKTER MANDIRI DAN TANGGUNG JAWAB ANAK MELALUI COOKING CLASS DI RA IMAMA MIJEN SEMARANG - Aan Widiyono; Erna Zumrotun; Siti Istiqomah. (Universitas Al-Hikmah Indonesia, 2022)
Character education values ​​need to be developed through independence and responsibility. Independence is defined as the attitude or behavior of individuals who are not easily dependent on others, while responsibility is an attitude or behavior to carry out activities seriously and be prepared to take all risks and actions. This study aims to determine the process of forming independent and responsible characters through cooking class activities which are carried out regularly every year. In addition, this research is expected to be able to describe the results of the process of cooking class activities at home and outside of school. This research is a quantitative descriptive study using a survey method via an online google form. The population of this study were parents of children in grade A3 at RA Imama. Cooking class activities are carried out directly at home and outside the school by taking into account the participation of parents in accompanying children's activities. The results showed that parental assistance was very influential on the independence and responsibility of children in cooking class activities, namely 93.75% more independent children, and 87.5% more responsible children. In addition, the response of parents in accompanying children in cooking class activities was in the very fun category, namely 87.5%.